Low Energy Electron Treatment - An Eco-Friendly Tool against Seed Borne Diseases - K VISHWANATH,; ANDRÉ WEIDAUER,; HM PALLAVI,; FRANK-HOLM ROEGNER,; RAMEGOWDA, (Seed Research, 2026)
Healthy seedlings are of prime importance for healthy crop growth. Numerous techniques are applied to obtain disease free seedlings. This paper concentrates on chemical-free methods as electron beam radiations to eradicate seed borne pathogens. The effect of accelerated electrons on pathogens and seed quality is reviewed. Low dose of electron beam and an exactly adjusted penetration depth, that don't reach the seed embryo, is found to be effective in controlling pathogen. Such new chemical free approaches for managing seed borne diseases are promising for organic farming. However, effect of electron beam varies with infection level and status of moisture level in seeds. This needs to be addressed to increase the potentiality of the electron treatment in ecological farming.